Sri Ksetra Museum Collection Inventory. - Galloway, Charlotte (Berlin/Boston : Walter de Gruyter GmbH, 2022)
Beyond Boundaries: Religion, Region, Language and the State is a research initiative hosted by the British Museum and the British Library in London. Moving beyond geographical, chronological, disciplinary and historiographical boundaries, the books in this series explore the interactions of India and her neighbors from late antiquity to the close of the medieval.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books